2002
DOI: 10.1046/j.1460-9568.2002.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery following peripheral destruction of olfactory neurons in young and adult mice

Abstract: Olfactory neurons (ON) which are located in the olfactory epithelium are responsible of odorous molecule detection. A unique feature of these cells is their continuous replacement throughout life due to the proliferation and differentiation of local neural precursors, the basal cells. Thus, experimental destruction of all ON induces a stimulation of basal cell division followed by tissue regeneration. The fact that ON precursors display such proliferative and neurogenic activity in adults makes these cells par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 56 publications
(78 reference statements)
8
49
0
Order By: Relevance
“…This can be achieved by irrigating the nasal cavity with a ZnSO 4 solution, causing widespread death of ORNs and triggering the simultaneous generation of new ORNs and their axons. Our description of the time course of degenerative events is broadly similar to the time courses reported in earlier studies after ZnSO 4 treatment (Cancalon, 1982;Burd, 1993;Chuah et al, 1995;Ducray et al, 2002) and methyl bromide inhalation (Schwob et al, 1995(Schwob et al, , 1999; however, we have extended the time frame of the analysis, examining simultaneous antigenic changes and correlating these with the inflammatory and proliferative responses throughout the olfactory system. We found that degeneration of the olfac- Fig.…”
Section: Discussionsupporting
confidence: 67%
“…This can be achieved by irrigating the nasal cavity with a ZnSO 4 solution, causing widespread death of ORNs and triggering the simultaneous generation of new ORNs and their axons. Our description of the time course of degenerative events is broadly similar to the time courses reported in earlier studies after ZnSO 4 treatment (Cancalon, 1982;Burd, 1993;Chuah et al, 1995;Ducray et al, 2002) and methyl bromide inhalation (Schwob et al, 1995(Schwob et al, , 1999; however, we have extended the time frame of the analysis, examining simultaneous antigenic changes and correlating these with the inflammatory and proliferative responses throughout the olfactory system. We found that degeneration of the olfac- Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Loss of OSNs Intranasal perfusion with ZnSO 4 has been used to induce OSN death in mice and rats to study recovery of OSNs following chemical lesion (Burd 1993;Herzog and Otto 1999). Ducray et al (2002) showed that mice could differentiate water and butanol in a behavioral test maze approximately 18 days following intranasal instillation of ZnSO 4 , indicating that an intact sense of smell was present. In that study, OMP staining was significantly reduced at 25 and 35 days after instillation in treated mice in spite of the recovery of olfactory-mediated behavior at 18 days.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that the extent of epithelial damage in olfactory mucosa and the increase in the threshold of olfactory perception in the same animal are not proportional, with only a small population of mature ORNs (<5% of the normal population) remaining or regenerating after experimental injury seeming to be sufficient to maintain the ability to detect odors (Ducray et al 2002;Youngentob et al 1997). This finding suggests that the peripheral olfactory system has a high level of spare ability, enabling the individual to maintain olfactory perception even when the olfactory mucosa is being damaged.…”
Section: Age-related Progression In Neuroepithelial Lesionmentioning
confidence: 98%
“…Clinically, olfactory disorder after upper respiratory viral infection, which is caused by the degeneration of the olfactory mucosa (Bihun and Percy 1995;Moran et al 1992;Yamagishi et al 1994), mainly occurs in the elderly population, with functional recovery tending to become increasingly incomplete with advancing age of the patient (Reden et al 2006;Temmel et al 2002). Anatomical recovery of olfactory neuroepithelium after experimental destruction also tends to be less complete with increasing age (Ducray et al 2002). These findings suggest that aged olfactory mucosa is more vulnerable to extrinsic insults and has a reduced capacity to restore normal structure and function following damage.…”
Section: Introductionmentioning
confidence: 99%